2011
DOI: 10.1111/j.1651-2227.2011.02213.x
|View full text |Cite
|
Sign up to set email alerts
|

Early‐onset pure absence epilepsy: a distinct epileptic syndrome

Abstract: Early-onset pure absence epilepsy is a distinct epilepsy characterized by absences starting from a few months to 4 years of age, normal early psychomotor development, good antiepileptic drug seizure control and normal intellectual outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Canafoglia and coworkers [ 40 ] that the enhanced outflow of frontal oscillations may be helpful to distinguish responders from non-responders. On the contrary, several other publications did not identify the EEG as a useful prognostic predictor [ 7 , 10 , 15 , 21 ]. Likewise, in our report no substantial prognostic difference was found between patients with or without focal EEG abnormalities, thus not supporting a relationship between focal dysfunctions and resistance to the ASM treatment.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Canafoglia and coworkers [ 40 ] that the enhanced outflow of frontal oscillations may be helpful to distinguish responders from non-responders. On the contrary, several other publications did not identify the EEG as a useful prognostic predictor [ 7 , 10 , 15 , 21 ]. Likewise, in our report no substantial prognostic difference was found between patients with or without focal EEG abnormalities, thus not supporting a relationship between focal dysfunctions and resistance to the ASM treatment.…”
Section: Discussionmentioning
confidence: 89%
“…The CAE subgroup was defined based on the ILAE Task Force 1989 criteria [ 14 ]: (1) onset of typical absences (TAs) before puberty in an otherwise normal child; (2) absence seizures as the predominant seizure type at time of diagnosis; (3) very frequent (several to many per day) absences; and (4) EEG showing bilateral, symmetrical spike-waves, usually 3 Hz, on normal background activity. Patients with TAs under the age of 3 were classified as “Early Onset Absence Epilepsy” (EOAE) and thus excluded from the study, since recent studies have considered it to be a distinct epileptic syndrome [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our study's primary goal was to test the neurocognitive performance of patients with CAE in comparison with healthy controls. In the studied sample we included only children who developed absence seizures above the age of four years, to exclude early‐onset pure absence epilepsy, which has earlier seizure onset than the typical CAE 17 . Also, in our study we excluded patients with history of generalised tonic‐clonic seizures or myoclonus and restricted it to right‐handed individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Less commonly, absence seizures may arise before the 4th year of age (Early-onset Absence Epilepsy), and may be associated with other neurological disorders (other types of seizures, developmental delay, and movement disorders) [60]. Recently it has been suggested that Early-onset pure absence epilepsy (EOAE) is a distinct epilepsy characterized by absences starting from a few months to 4 years of age, normal early psychomotor development, good AEDs seizure control and normal intellectual outcome [61]. …”
Section: Introductionmentioning
confidence: 99%